Substitution of Boiled Purple Sweet Potato in Making Purple Doughnut - Hengki Wijaya; Jeffly Ramsaleh; Griselda Prisilia Patandi (Khaliya Onomiyea: Jurnal Abdimas Nusantara, 2023)
This paper is the outcome of food products from entrepreneurship lessons. This part becomes fascinating because the essential ingredients of doughnuts are made from purple sweet potato, which substitutes wheat flour. Purple sweet potato provides health benefits. The method is qualitative with an organoleptic test approach for purple doughnut products and a SWOT test to evaluate the product before it is marketed. The availability of raw materials is the strength of this doughnut product. The organoleptic test assessment stands out in the doughnut colour and texture category with a preference level of 95.44% and 90.9%, respectively. This innovation produces doughnuts with the preferred purple filling colour.